New pairings and deorphanization among the atypical chemokine receptor family — physiological and clinical relevance - Szpakowska, Martyna; D’Uonnolo, Giulia; Luís, Rafael; Alonso Bartolomé, Ana; Thelen, Marcus; Legler, Daniel F.; Chevigné, Andy (Frontiers in Immunology, 2023)
Atypical chemokine receptors (ACKRs) form a small subfamily of receptors (ACKR1–4) unable to trigger G protein-dependent signaling in response to their ligands. They do, however, play a crucial regulatory role in chemokine biology by capturing, scavenging or transporting chemokines, thereby regulating their availability and signaling through classical chemokine receptors. ACKRs add thus another layer of complexity to the intricate chemokine–receptor interaction network. Recently, targeted approaches and screening programs aiming at reassessing chemokine activity towards ACKRs identified several new pairings such as the dimeric CXCL12 with ACKR1, CXCL2, CXCL10 and CCL26 with ACKR2, the viral broad-spectrum chemokine vCCL2/vMIP-II, a range of opioid peptides and PAMP-12 with ACKR3 as well as CCL20 and CCL22 with ACKR4. Moreover, GPR182 (ACKR5) has been lately proposed as a new promiscuous atypical chemokine receptor with scavenging activity notably towards CXCL9, CXCL10, CXCL12 and CXCL13. Altogether, these findings reveal new degrees of complexity of the chemokine network and expand the panel of ACKR ligands and regulatory functions. In this minireview, we present and discuss these new pairings, their physiological and clinical relevance as well as the opportunities they open for targeting ACKRs in innovative therapeutic strategies.